Preparation of catalysts for olefin oligomerization reaction (2017)
RESUMEN: Carbon templated zeolites have been used as catalysts systems to gain knowledge into the effect that templating method has on porosity, acidity and reactivity of the zeolites. Moreover, secondary synthesis, namely impregnation and isomorphous substitution with chromium and phosphorus were employed to understanding the role of these ions at the different pore size scales. For this purpose, a set of medium and large pore zeolite powders (MFI, BEA and FAU) have been studied with bulk characterization techniques in combination with catalytic activity in propylene oligomerization and methanol to olefins reactions. In Chapter 3 the effect that carbon templating method has on the physicochemical properties of ZSM-5 zeolite has been investigated and correlated with reactivity in propylene oligomerization reaction. This approach has shown that incorporation of carbon nanotubes as a second template in the hydrothermal synthesis of zeolites causes significant surface roughening accompanied by the formation of mesopores, and erosion of silanol nest. Moreover, the generation of a mesoporous network throughout the zeolites induced the long time life of the catalysts in the propylene oligomerization reaction. Insights of these modifications has also been obtained in Chapter 4 and 5 for large pore BEA(Beta) and FAU(Y) zeolites. It has been found that the pore accessibility and acid density increased after using carbon nanotubes as a second template in hydrothermal synthesis. The reactivity during the propylene oligomerization reaction revealed a faster deactivation due to a highly accessibility of bulky molecules, which are sensitive to parallel reactions like cracking and hydride transfer. In this manner, the lower stability of these zeolites are related to the presence of carbon phases. Nevertheless, the generation of additional porosity implied an increase of the catalysts lifetime during the reaction in comparison with their microporosity BEA(Beta) and FAU(Y) counterparts. Additional to the mesopores creation an additional heterogeneity in zeolites was achieved by the modification in chemical composition. To this end, impregnation and isomorphous substitution methods with chromium and phosphorus were applied for each molecular sieve MFI(ZSM-5), BEA(Bea) and FAU(Y). Structural characterization by X-Ray diffraction, diffuse reflectance spectroscopy and Raman spectroscopy showed that chromium and phosphorus ions were located in two ways: (i) as clusters in the surface of the zeolites when the method employed was impregnation, and (ii) isomorphously substituted ions in the structure or distributed ions into the pores when the method employed was isomorphous substitution. Moreover, we found different trends in the reaction performance. It has been found the presence of polychromate like-structures are responsible for an improved in conversion and tetramers selectivity during the propylene oligomerization reaction. In contrast, P series zeolites causes a significant decrease in concentration of strong acid sites, which limits the change of olefins undergoing hydride transfer and cyclization reactions. In Chapter 6, the effect that carbon templating and non-templating method (desilication) has on the physicochemical properties and reactivity of ZSM-5 catalyst powders during the methanol to olefins (MTO) reaction has been investigated with a combination of UV-Vis microscopy and a series of bulk characterization techniques. The lower stability displayed by the parent ZSM-5 catalyst powder finds its origin in the diffusion limitations induced by the presence of polyaromatic species into the pores of catalyst. With this approach, it was found that templating and non-templating method leads to an improved of stability in the reaction. It has been revealed that this modification improves the diffusion properties of zeolite ZSM-5 catalyst powders, while minimizing undesired consecutive reactions. Carbon templated HZSM-5 zeolite present a high selectivity towards light olefins with a high performance in the timeframe. Nevertheless, desilicated zeolite showed a limited conversion of methanol due to a modification in the concentration of strong acid sites. In Chapter 7, as a part of sustainable development, among different recycling application of coal combustion byproducts, zeolitization was a preparation process choose to reducing the volume of waste materials and environmental impact. The hydrothermal modifications to coal combustion byproducts tend to impart very important enhancement on chemical catalyst processes. This study should enable investigations of the MFI type zeolites that form from specific raw materials, and the interacting metal influence on the catalytic activity propylene oligomerization. Based on the summary points described above, several important conclusions can be made regarding to: (i) the presence of heterogeneities, namely chemical composition and porosity within zeolites; (ii) the differences in catalytic performance taking place during propylene oligomerization for small and large pore carbon templated zeolites, (iii) the differences in catalytic performance taking place during propylene oligomerization for chromium and phosphorus promotion in carbon templated zeolites, (iv) the catalytic performance taking place during MTO reaction within templated and non-templated ZSM-5 zeolite, and (v) catalytic activity of zeolites synthesized from coal combustion byproducts in propylene oligomerization.